Spatial Differentiation of the Population Ageing Process in Poland - Majdzińska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The main aim of the article was to analyse the changes in the Polish population structure observed since the political transformation and expected in the next few years. The analysis focused also on the spatial differentiation of both processes, population ageing (indicated with several measures) and dynamics of population ageing in Poland in the years 2002, 2014, 2020, which were conducted at the level of voivodships, poviats and gminas. The statistical data concerning the age structure in Poland were provided by the Central Statistical Office in Poland.